Calorie Restriction Rescues Mitochondrial Dysfunction in Adck2-Deficient Skeletal Muscle - Hernández-Camacho, Juan Diego; Fernández-Ayala, Daniel J. M.; Vicente-García, Cristina; Navas-Enamorado, Ignacio; López-Lluch, Guillermo; Oliva, Clara; Artuch, Rafael; Garcia-Villoria, Judith; Ribes, Antonia; de Cabo, Rafael; Carvajal, Jaime J.; Navas, Plácido (Frontiers in Physiology, 2022)
ADCK2 haploinsufficiency leads to a coenzyme Q deficiency in skeletal muscle mitochondria, causing a myopathy associated with defects in beta-oxidation of fatty acids, aged-matched metabolic reprogramming, and defective physical performance. Caloric restriction has proven to preserve function and increase lifespan delaying the onset of most chronic diseases. To study the possible impact of calorie restriction (CR) on heterozygous Adck2 knockout mice were fed under 40% CR and the phenotype was followed for 7 months. CR was able to restore glucose and fatty acids metabolism in muscle to those of wild type littermates. Metabolomic analysis showed the partial rescue of the metabolite profiles of mutant mice by CR. Isolated mitochondria from skeletal muscle demonstrated that CR increased both CoQ levels and oxygen consumption rates (OCR) indicating a shift towards more oxidative fiber type in skeletal muscle, in mutant muscles, reaching WT levels. To further characterize the impact of CR over muscle, we studied satellite cells induced to differentiation in culture media containing serum obtained from ad libitum or CR animals. Under this conditions, mutant cells on AL media showed a lower myotube differentiation, growth, and decreased oxygen consumption. However, mutant cells grown on CR serum exhibited levels reaching those of WT cells, with a recovery of respiration measured by OCR. The overall in vitro restauration of skeletal muscle bioenergetics by CR was paralleled by the improvements of physical performance in vivo. These results support the potential role for a CR intervention to recover the defective aerobic metabolism and differentiation of skeletal muscle in mice caused by Adk2 haploinsufficiency.